Differences in the Quality of Health Services on the Satisfaction of BPJS Health Users - Widya Cahyaningsih Polontalo; Herlina Jusuf; Suardi Suardi (Indonesian Journal of Global Health Research, 2026)
The quality of healthcare services plays a crucial role in determining patient satisfaction, especially among BPJS Kesehatan users at primary healthcare facilities. This study aims to examine differences in service quality and healthcare workers’ workload and their relationship with patient satisfaction at the Kota Tengah Health Center and Medy’s Primary Clinic in Gorontalo City. This quantitative study employed an associative analytic design involving 324 respondents selected through accidental sampling. Data were collected using structured questionnaires that had undergone validity testing using item–total correlations (items accepted when r-count > r-table, p < 0.05) and reliability testing using Cronbach’s Alpha, with coefficients ≥ 0.70 indicating acceptable internal consistency. Data were analyzed using appropriate statistical tests, including bivariate correlation and t-tests. The findings revealed significant differences in service quality, workload, and patient satisfaction between the two healthcare facilities. The Kota Tengah Health Center demonstrated superior service quality, particularly in the dimensions of patient safety, effectiveness, and timeliness. At the Health Center, patient-centeredness was the strongest predictor of patient satisfaction (r = 0.891; R² = 79.4%). In contrast, at Medy’s Primary Clinic, healthcare workers’ workload had the greatest influence on patient satisfaction (r = 0.611; R² = 37.4%). A t-test further indicated that overall patient satisfaction was significantly higher at the Health Center (p = 0.000). Both service quality and healthcare workers’ workload significantly influence patient satisfaction.